Introduction - Paczolay, Péter (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
The acceptance of the universality of human rights, and their enforcement by supranational institutions, including courts, developed in a contradictory context. There is a tension between the majoritarian democratic institutions and the non-majoritarian judicial bodies. This legitimacy challenge becomes even more difficult in the relation of an international court ruling over sovereign member states. But the Strasbourg court could soften this difficulty by playing a subsidiary role in cases where the breach of the Convention is not remedied at the national level. The chapter presents the reasons for the historical development of the European institutions for the protection of human rights: democracy through human rights, political freedom and the rule of law. Nowadays, the Court refers to the Convention as a “living instrument”, the Court interprets the provisions of the Convention in a deliberately evolutionary matter, in accordance with the spirit of the Convention.Keywords: Subsidiarity, European mechanisms for protection of human rights, universalism of human rights, counter-majoritarian difficulty